2020
DOI: 10.1007/s12517-020-05872-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of soil–structure interaction on the fundamental frequency of shear wall structures

Abstract: Numerous studies indicate that soil-structure interaction has a great influence on the dynamic characteristic of buildings. This study presents an analysis of the effect of soil-structure interaction (SSI) on the natural frequency of shear wall building structures. The system is modeled by a 3D finite element model and using elastic discrete springs to represent the soilstructure interaction. A parametric study for different soil profiles is performed on one-storey building followed by a generalization on mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…With "nonlinear time history" study results as a benchmark, the proposed machine learning technique outperformed fixed-base as well as ASCE 7-16 approaches. The findings demonstrated that, when compared to fixed-base, SVM, along with ASCE 7-16 linear SSI approaches, the results of the SSI-based ANN system have been in good alignment with "nonlinear time history" analysis [53].…”
Section: Rc Buildings' Seismic Vulnerability In the Impacts Of Ssimentioning
confidence: 85%
“…With "nonlinear time history" study results as a benchmark, the proposed machine learning technique outperformed fixed-base as well as ASCE 7-16 approaches. The findings demonstrated that, when compared to fixed-base, SVM, along with ASCE 7-16 linear SSI approaches, the results of the SSI-based ANN system have been in good alignment with "nonlinear time history" analysis [53].…”
Section: Rc Buildings' Seismic Vulnerability In the Impacts Of Ssimentioning
confidence: 85%
“…A simplified model of large pile groups and super-tall buildings considering the SSI was established, and the dynamic response of super-tall buildings to wind loads considering the SSI was investigated [27]. Sadek et al [28] analyzed the influence of soil-structure interaction on the natural frequency of shear wall structures. The seismic collapse capacity of steel frame structures considering the SSI was studied [29].…”
Section: Introductionmentioning
confidence: 99%